Political Risk Paths in International Construction Projects: Case Study from Chinese Construction Enterprises - Tengyuan Chang; Xiaopeng Deng; Bon-Gang Hwang; Xiaojing Zhao (Advances in Civil Engineering)
International construction enterprises (ICEs) have been plagued with political risks in the global market. To ensure the success of political risk management, it is necessary to comprehend the political risks in international construction projects. This study aims at exploring the political risk paths in international construction projects. The preliminary political risk factors and paths were proposed from the literature review. A survey questionnaire was developed to collect political risk cases faced by Chinese construction enterprises (CCEs) performing international construction projects, and 264 valid cases were received and analyzed for this study. Adopting the confirmatory factor analysis (CFA) method, 6 macrofactors (“sociopolitical stability” (A), “legal and regulatory” (B), “social safety” (C), “economy performance” (D), “attitude towards foreigners” (E), and “international environment” (F)) and 2 microfactors (“low exposure” (G) and “capability of enterprises” (H)) were identified. Moreover, the results of path analysis illustrated that 7 factors (A, B, C, D, E, G, and H) had the significant direct negative effect on “risk consequences” and 3 factors (A, D, and F) had the indirect negative effect on “risk consequences.” The findings from this study help practitioners gain an in-depth understanding of political risks in international construction projects and provide a useful reference for ICEs to manage political risks when venturing outside their home countries.